It's not you eaudiobook Identifying and healing from narcissistic people. - Durvasula, Ramani (Books on Tape, 2024)
INSTANT NEW YORK TIMES BESTSELLER From clinical psychologist and expert in narcissistic relationships Dr. Ramani Durvasula, a guide to protecting and healing yourself from the daily harms of narcissism AN OPEN FIELD PUBLICATION FROM MARIA SHRIVER It’s not always easy to tell when you’re dealing with a narcissistic person. One day they draw you in with their charm and charisma, the next they gaslight you, wreck your self-esteem, and leave you wondering, What should I have done differently? As Dr. Ramani explains in It’s Not You , the answer is: absolutely nothing. Just as a tiger can’t change its stripes, a narcissist will not stop manipulating and invalidating you, no matter how much you try to appease them. The first step toward healing from their toxic influence—and to protect yourself from future harm—is to accept that you are not to blame for their behavior. Drawing on more than two decades of studying the landscape of narcissism and working with survivors, Dr. Ramani explores how narcissists hijack our well-being and offers a healing path forward. Unpacking the oft-misunderstood personality, she reveals the telltale behavioral patterns that indicate you may be dealing with a narcissist. Along the way, you’ll learn how to become gaslight resistant, chip away at the trauma bonds that keep you stuck in the cycle, grieve the loss of these painful relationships, create and maintain realistic boundaries, discern unhelpful behaviors from narcissistic behaviors, and recover your sense of self after constant invalidation. Thriving after, or even during, a narcissistic relationship can be challenging, but It’s Not You shows you it is possible. Dr. Ramani invites you to stop blaming yourself and trying to change the narcissistic person, and to start giving yourself permission to let go of their hold on you and finally embrace your true self.